Urban dreams and economic realities – Areas of innovation between the demands of the knowledge society and the requirements of innovative industries - Sascha Brinkhoff; Robert Kitzmann (31st IASP World Conference: Conference Proceedings, 2014)
The attractiveness of high-technology companies for skilled, creative and international talent is one of the most important factors for their global competitiveness. Recent research shows that highly skilled people increasingly demand their work place to be a place to work, live and socialize - thus, a more urban environment. As recent developments in metropolitan areas show, cities in general are challenging the classical model of science and technology parks. In three Berlin-based case studies the authors have undertaken a survey and expert interviews examining the image and perception of the respective area of innovation as well as the role of multifunctional urbanism in the generation of innovation and new knowledge. However the authors argue that STPs and areas of innovation will and should not become like cities entirely. They need to maintain their profile and USP as distinct knowledge and innovation hubs to generate long-term economic, real tech-based growth and R&D based innovation.
Keywords: 330; Areas of innovation; Science parks; Kowledge society; Urbanism; Innovation; Technology parks; Berlin; Adlershof; Charlottenburg; Berlin-Buch